Comparison of Gluteus Maximus, Hamstring and Multifidus Muscle Activities During Bridge Exercises According to Three Different Hip Abduction Angles - Ji-Seok Choi; Tae-Jin Jang; In-Cheol Jeon (Korean Research Society of Physical Therapy, 2022)
Background: Muscle activities of gluteus maximus (GM) and hamstring (HAM) have important roles in the stability and mobility of the hip joint during various functional activities including bridge and prone hip extension exercises. Objects: The purpose of this study is to investigate muscle activities of GM, multifidus (MF) and HAM during three different bridge exercises in healthy individuals. Methods: Twenty healthy subjects were participated. Electromyography device was used to measure muscle activities of GM, MF and HAM. Each subject was asked to perform three different bridge exercises with hip abduction (0°, 15°, 30°) in random order. One-way repeated measures analysis of the variance and a Bonferroni post hoc test were used. Statistical significance was set at α = 0.01. Results: The muscle activity of GM was significantly different among three conditions (hip abduction 0°, 15°, 30°) (adjusted p-value [Padj] < 0.01). The muscle activity of GM was significantly greater during bridge exercise with hip abduction 30° compared to 0° and 15° (Padj < 0.01). There was no significant difference in the muscle activity of MF and HAM muscle (Padj > 0.01). The ratio of muscle activity (ratio = GM/HAM) during bridge exercise with hip abduction 30° was significant greater compared to the hip abduction angles 0° and 15° (Padj < 0.01). Conclusion: Bridge exercise with hip abduction 30° can be recommended to selectively facilitate the muscle activity of GM and improve the ratio of muscle activity between GM and HAM.